Duplex Ultrasonography for the Evaluation of Extracranial Vertebral Artery: A Prospective Comparison With Digital Subtraction Angiography - Zhang, Jie; Xing, Yingqi; Cui, Li (Frontiers in Neurology, 2022)
Background and Objective: Patients with symptomatic vertebral artery stenosis are at high risk of stroke recurrence, especially ≥70% stenosis. Revascularization may be considered for extracranial vertebral artery stenosis in patients with recurrent ischaemic events despite optimal medical management. Currently, there is a lack of consensus on the ultrasonic evaluation of extracranial vertebral artery stenosis in clinical practice. This study aimed to validate the efficiency of duplex ultrasonography and assess the optimal sonographic thresholds for predicting extracranial vertebral artery stenosis. Methods: This is a prospective study of all patients with symptomatic posterior circulation stroke/transient ischemic attack who were scheduled to undergo digital subtraction angiography from April 2020 to October 2021. A total of 544 vertebral arteries with normal lumen or extracranial stenosis confirmed with digital subtraction angiography were included in the study. The peak systolic velocity at V1 segment (PSVv1) and V2 segment (PSVv2) were measured and the PSVv1/PSVv2 and PSVv2/PSVv1 ratios were calculated. Results: The cutoff values for predicting ≥50% and ≥70% V1 segment stenosis were PSVv1 ≥146 cm/s (sensitivity 76.2%, specificity 86.3%) and PSVv1/PSVv2 ratio ≥2.2 (sensitivity 84.3%, specificity 77.6%), and PSVv1 ≥184 cm/s (sensitivity 80.8%, specificity 87.1%) and PSVv1/PSVv2 ratio ≥3.5 (sensitivity 79.5%, specificity 90.5%), respectively. And the cutoff values for predicting ≥50% and ≥70% V2 segment stenosis were PSVv2 ≥80 cm/s (sensitivity 75.0%, specificity 91.0%) and PSVv2/PSVv1 ratio ≥1.2 (sensitivity 75.0%, specificity 94.8%), and PSVv2 ≥111 cm/s (sensitivity 81.0%, specificity 95.0%) and PSVv2/PSVv1 ratio ≥1.7 (sensitivity 81.0%, specificity 96.6%), respectively. Conclusions: Symptomatic patients with the ultrasonic parameters of PSVv1 ≥146 cm/s and PSVv1/PSVv2 ratio ≥2.2 at V1 segment or PSVv2 ≥80 cm/s and PSVv2/PSVv1 ratio ≥1.2 at V2 segment need to be considered for further verification by digital subtraction angiography to seek revascularization. If the parameters increase to PSVv1 ≥184 cm/s and PSVv1/PSVv2 ratio ≥3.5 at V1 segment or PSVv2 ≥111 cm/s and PSVv2/PSVv1 ratio ≥1.7 at V2 segment, these patients have an increased risk of recurrent stroke and are more likely to need revascularization. The results can be used as a reference for the assessment and long-term management of patients with extracranial VA stenosis.